The gray area between operational tolerance and overt rejection in kidney transplantation - Rui F. Silva; Miguel L. Relvas; Ana Nunes; José L. Silvano; Ana Beco; Manuela B. Bustorff; Susana M. Sampaio (Publicações Ciência e Vida, 2021)
Operational tolerance in kidney transplantation is characterized by stable serum creatinine < 1.7 mg/dL and proteinuria < 1 g/day in the absence of immunosuppression or immunodeficiency for over one year. However, simultaneous donor specific antibodies are common and serum creatinine is a poor surrogate of early lesions. Consequently, subclinical rejections will meet operational tolerance criteria if sérum creatinine remains stable. We report a patient with operational tolerance criteria followed by biopsy-proven chronic active antibody mediated rejection, discussing the intricate challenges of immunosuppression management.